1988
DOI: 10.1523/jneurosci.08-05-01500.1988
|View full text |Cite
|
Sign up to set email alerts
|

Functional anatomy of macaque striate cortex. I. Ocular dominance, binocular interactions, and baseline conditions

Abstract: A series of experiments was carried out using 14C-2-deoxy-d-glucose (DG) in order to examine the functional architecture of macaque striate (primary visual) cortex. This paper describes the results of experiments on uptake during various baseline (or reference) conditions of visual stimulation (described below), and on differences in the functional architecture following monocular versus binocular viewing conditions. In binocular “baseline” experiments, monkeys were stimulated either (1) in the dark, (2) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
114
1

Year Published

1989
1989
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(138 citation statements)
references
References 28 publications
23
114
1
Order By: Relevance
“…Similar to the ODC maps in the monkey (26,33,34) and previous human anatomical (16,35) and functional (19,21) studies, preferences to right vs. left eye stimulation were observed as parallel bands modulating in 2-mm cycles (21). We have also demonstrated that such ODC maps are reproducible over days (21).…”
Section: Resultssupporting
confidence: 86%
“…Similar to the ODC maps in the monkey (26,33,34) and previous human anatomical (16,35) and functional (19,21) studies, preferences to right vs. left eye stimulation were observed as parallel bands modulating in 2-mm cycles (21). We have also demonstrated that such ODC maps are reproducible over days (21).…”
Section: Resultssupporting
confidence: 86%
“…Moreover, those metabolic responses (here, glucose consumption) and neuronal activity were tightly co-localized (Sokoloff, 1981), as demonstrated by the high resolution of functional maps obtained in cat and monkey using the 2DG method (Kennedy et al, 1976;Tootell et al, 1981Tootell et al, , 1982Tootell et al, , 1988, as well as by staining selec- Figure 1. High-resolution functional optical imaging reveals the relationship between pinwheels "detection of orientated edges, shape processing…, ocular dominance columns "stereo vision, depth processing…, and cytochrome oxidase blobs "color vision… in the primary visual cortex of the macaque monkey.…”
Section: Neuronal Activity Evokes Metabolic and Haemodynamic Responsesmentioning
confidence: 84%
“…Each module contains a complete set of about 60,000 neurons, processing the three features of orientation, depth, and color. ͑Modified from Bartfeld and Grinvald, 1992.͒ tively for cytochrome oxidase (Tootell et al, 1983(Tootell et al, , 1988, an enzyme that participates in the mitochondrial respiratory chain and thus accumulates in loci of increased metabolic activity. Spatial resolution of those methods easily attains the sub-millimeter scale, allowing the abovementioned cortical columns to be clearly visualized.…”
Section: Neuronal Activity Evokes Metabolic and Haemodynamic Responsesmentioning
confidence: 99%
“…Familiar examples include the ocular dominance (39,40) and orientation columns in V1 (41), orientation-and colorsegregated columnar stripes in V2 (42,43), columns for direction of motion in MT/V5 (44), and subregions for object-related properties and face selectivity in the inferior temporal (IT) cortex (12,27,45). Presumably, columns/patches arise because such an architecture allows shorter axonal connections between neurons that require a great deal of interaction-i.e., functionally similar neurons.…”
Section: Discussionmentioning
confidence: 99%